The Effectiveness Of Administrative Review In Indonesia’S Administrative Court System - Dani, Umar (Prophetic Law Review, 2019)
This research aims to describe the use of administrative review in Indonesia. There are two rules of administrative review: administrative review according to Act Number 5 Year 1986 on State Administrative Judicial Action, and administrative review according to Act Number 30 Year 2014 on Government Administration. Both of these rules contradict each other and are equally authorized at the same time, and thus, in practice, we must determine which regulation is the most appropriate to use as a legal basis. This study analyzes the use of administrative review and its effectiveness in providing legal protection. To discuss these issues, the researcher has used normative or dogmatic legal research method. The results of the study show that in general, administrative review procedure has applied the system as determined in Act Number 30 Year 2014 on Government Administration, except those specifically regulated by Act No 5, such as personnel disputes. The new version of Administrative review does not provide effective legal protection because the process of resolving state administrative disputes is lengthy and does not comply with the principles and theories of administrative review in general terms.Keywords: Administrative law; administrative review; objection; State Administrative Court.Efektivitas Pengujian Administratif dalam Sistem Peradilan Tata Usaha Negara IndonesiaAbstrakPenelitian ini bertujuan untuk mendeskripsikan penggunaan administrative review (pengujian administratif) di Indonesia. Ada dua aturan terkait pengujian administratif, yaitu: pengujian administratif menurut Undang-Undang Nomor 5 Tahun 1986 tentang Peradilan Tata Usaha Negara; dan pengujian administratif menurut Undang-Undang Nomor 30 Tahun 2014 tentang Tata Usaha Negara. Kedua aturan ini sama-sama berwenang namun saling bertentangan sehingga dalam praktiknya kita harus menentukan aturan mana yang paling tepat untuk dijadikan landasan hukum. Studi ini menganalisis penggunaan pengujian administratif dan efektivitasnya dalam memberikan perlindungan hukum. Untuk membahas permasalahan tersebut, peneliti menggunakan metode penelitian hukum normatif atau dogmatis. Hasil kajian menunjukkan bahwa secara umum tata cara pengujian administratif telah menerapkan sistem sebagaimana diatur dalam Undang-Undang Nomor 30 Tahun 2014 tentang Administrasi Negara, kecuali yang secara khusus diatur dalam Undang-Undang Nomor 5 Tahun 1986 tentang Peradilan Tata Usaha Negara, seperti sengketa kepegawaian. Bentuk baru pengujian administratif tidak memberikan perlindungan hukum yang efektif karena proses penyelesaian sengketa tata usaha negara yang panjang dan tidak sesuai dengan prinsip dan teori kajian administrasi secara umum.Kata kunci: Hukum Administrasi; Keberatan; Pengadilan Tata Usaha Negara; Pengujian Administrasi